2010
DOI: 10.1111/j.1365-2516.2010.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin isotypes and functional anti-FVIII antibodies in response to FVIII treatment in Balb/c and C57BL/6 haemophilia A mice

Abstract: Previous studies have demonstrated that genetic factors play an important role in determining the likelihood of formation of anti-factor VIII (FVIII) antibodies in haemophilia A patients. We were interested in characterizing the spectrum of FVIII antibody formation and the primary and secondary immune responses after FVIII administration in two different exon 16-disrupted haemophilia A mouse strains, Balb/c and C57BL/6. Balb/c and C57BL/6 E16 haemophilia A mice were used in all experiments. Total FVIII antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
5
32
0
Order By: Relevance
“…Our findings on the different isotype preferences by the 2 strains of HemA mice are consistent with previous reports. 29 We confirmed tolerance induction could also be achieved in HemA mice when hFVIII-alum was administered subcutaneously and the anti-CD4 mAb intravenously ( Figure 3F). …”
Section: Resultssupporting
confidence: 59%
“…Our findings on the different isotype preferences by the 2 strains of HemA mice are consistent with previous reports. 29 We confirmed tolerance induction could also be achieved in HemA mice when hFVIII-alum was administered subcutaneously and the anti-CD4 mAb intravenously ( Figure 3F). …”
Section: Resultssupporting
confidence: 59%
“…25,26 Furthermore, the adjuvanted-vaccine modulation of the anti-FVIII response with the associated increase in plasma levels of FVIII-specific IgG1 suggest that the addition of the M59 adjuvant alters the Th profile to a predominately Th2 response, a role that has previously been suggested. 27,28 However, these results may be strain specific as it has For personal use only. on May 9, 2018. by guest www.bloodjournal.org From been suggested that the role of MF59 is to simply augment the default immune profile rather than biasing the profile.…”
Section: Discussionmentioning
confidence: 86%
“…31,32 To date, there is no conclusive evidence on distinct rates of inhibitor formation comparing recombinant BDD or full-length FVIII. 8 Moreover, the B-domain sequence is the most polymorphic of all the FVIII domains.…”
Section: Discussionmentioning
confidence: 99%